Investigation on different driving cycle and scenarios considering the autonomous electric vehicles - DEMİR, UĞUR (My University, 2022)
This study presents a series of analyzes considering the traction and steering demands of an autonomous electric vehicle (AEV) as a shuttle. The considered analyzes in here are dealt with as driving cycle (DC) and driving scenarios (DS) to assess the traction and steering perfor-mance of the AEV. The aim of this study is to evaluate the issues such as over engineering for AEV traction and steering motor requirements on a certain route by comparatively analyzing traditional and dynamic calculation under the DC and DS. Therefore, DC and DS in the liter-ature are evaluated in terms of different applications, optimization techniques, generation al-gorithm, parametric characterization, e-motor type etc. Afterwards, NEDC, US06, WLTC, Double Lane Change (DLC), Constant Radius (CR) and Slowly Increase Steer (SIS) are de-termined. Then, they are arranged according to the vehicle-specific limits on an electric golf car. The modified DCs and DSs are run on the dynamic model of the vehicle. In the performed analysis, the parameters such as reference trajectory tracking, yaw angle, tractive and steering forces, lateral and longitudinal displacement-acceleration, steering and traction motor power—speed-torque are investigated. Then the obtained results are evaluated by comparing the tra-ditional calculation results.
Keywords: Driving cycle; Driving Scenario; Autonomous Vehicle; Steering and Traction Dynamics.